Extra-Pontine Myelinolysis in a Patient with Diabetes Insipidus Secondary to Disgerminoma of the Central Nervous System: Case Report - Araújo, Bruno Espírito Santo de (2018)
Introduction: Osmotic demyelination syndrome is a rare neurological condition caused by damage to the myelin sheath of neurons, involving difficulty in the management of sodium imbalance in patients with diabetes insipidus. Case report: Patient was a 14-year-old female with diabetes insipidus secondary to dysgerminoma of the central nervous system, with severe hyponatremia (sodium 103 mEq/L). Five days after rapid correction of the sodium imbalance, the patient presented coma (Glasgow scale:11), dysphagia, mutism, and quadriparesis. Cranial MRI findings were consistent with a diagnosis of extrapontine myelinolysis. Twenty-five days after admission to the ICU, the patient was alert, oriented, walking without difficulty, eating an oral diet without choking, although with slightly diminished strength in the upper limbs and slightly sluggish verbal communication. Three-month follow-up MRI showed atrophy of the basal nuclei, confirming severe cellular injury. Conclusion: Presentation of osmotic demyelination may range from mild or asymptomatic clinical forms to severe motor sequelae and death. There is no specific treatment, which highlights the importance of early diagnosis and adequate management of the sodium imbalance, as well as rigorous control of serum sodium levels.